Climate change disrupts local adaptation and favours upslope migration. (14th November 2019) - Anderson, Jill T.; Wadgymar, Susana M.
Abstract: Contemporary climate change is proceeding at an unprecedented rate. The question remains whether populations adapted to historical conditions can persist under rapid environmental change. We tested whether climate change will disrupt local adaptation and reduce population growth rates using the perennial plant Boechera stricta (Brassicaceae). In a large‐scale field experiment conducted over five years, we exposed > 106 000 transplants to historical, current, or future climates and quantified fitness components. Low‐elevation populations outperformed local populations under simulated climate change (snow removal) across all five experimental gardens. Local maladaptation also emerged in control treatments, but it was less pronounced than under snow removal. We recovered local adaptation under snow addition treatments, which reflect historical conditions. Our results revealed that low elevation populations risk rapid decline, whereas upslope migration could enable population persistence and expansion at higher elevation locales. Local adaptation to historical conditions could increase vulnerability to climate change, even for geographically widespread species. Abstract : Here, we provide direct evidence that climate change has disrupted long‐standing patterns of local adaptation, favoring plants that evolved under hot and dry conditions. Previous empirical studies have suggested that climate change may induce maladaptation, but they have not included direct manipulations of climatic factors to document the extent to which populations were historically locally adapted or the degree to which climate change alters those patterns. Our revised manuscript fills key gaps in the literature by experimentally (1) recovering local adaptation under historical climate conditions, (2) establishing that climate change had already generated maladaptation and will continue to do so, and (3) revealing that upslope and migration could rescue populations demographically.